The INFLUENCE OF BRAND IMAGE AND SERVICE QUALITY ON THE DECISION TO PURCHASE A HOUSE WITH MODERATING EFFECT OF LIFESTYLE: A CASE STUDY ON MORTGAGE LOANS AT BANK TABUNGAN NEGARA BRANCH OFFICE, KABUPATEN BUNGO - Sihombing, Jul Kono; Octavia, Ade; Fitriaty, Fitriaty (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
This study analyzes the influence of brand image, service quality, and lifestyle on the decision to finance home ownership loans (KPR) at Bank Tabungan Negara (BTN) in Kabupaten Bungo. Data were collected through questionnaires distributed to BTN customers who have taken out KPR. Data analysis was performed using multiple regression techniques. The results show that brand image and service quality have a positive and significant influence on KPR financing decisions. Additionally, lifestyle moderates the relationship between brand image and KPR financing decisions, as well as between service quality and KPR financing decisions. These findings highlight the importance of enhancing brand image and service quality and considering customer lifestyle in designing KPR products and services.